Imaging Features of Breast Periductal Stromal Tumor: A Case Report - Ding, Ning; Jiang, Ying; Liu, Haimin; Zheng, Fuling; Zhu, Shenling; Wang, Ming; Yang, Meng; Kong, Lingyan; Xue, Huadan; Jin, Zhengyu (Frontiers in Oncology, 2021)
Breast periductal stromal tumor(PDST) is a rare biphasic tumor, originated from periductal stromal, PDST demonstrates both benign ductal epithelium and nonphyllode sarcomatous stroma. Because of the rareness of PDST, its radiological features were rarely reported. In this study, we represent a case of PDST with full-field digital mammography (FFDM), digital breast tomosynthesis (DBT), and ultrasonography (US) descriptions. A 48-year-old woman was presented to our hospital with a recent enlarging right breast mass. The main imaging features were: 1. multiple solid, lobulated lesions behind the nipple-areolar complex of the right breast; 2. US revealed hypoechoic heterogeneous masses with internal separations and abundant blood flow; 3.FFDM and DBT showed multiple hyper intensified nodules, some were fused. The patient underwent surgery, the final pathology confirmed a periductal stromal tumor (PDST).